Comparative Analysis of Flipped Classroom and Traditional Learning on Academic Performance: Kenyatta University Case Study - Misal, Vaibhav (Journal of Educational Research and Policies, 2025)
This paper investigated the effects of flipped classroom learning on students’ academic performance, compared to traditional face - to - face learning in Kenyatta University. It was guided by the constructivist learning and cognitive load theories and adopted the descriptive research design. The target population was 5 heads of departments in the School of Education and 145 second year students pursuing post–graduate diploma in education at Kenyatta University. The census method was used to select the 5 heads of department who were involved in the study while Slovin’s formula, proportionate and simple random sampling techniques were used to select a sample of 106 students. A questionnaire was used to collect data from departmental heads while an interview schedule was used to gather data from the students. Frequencies and percentage were used to summarize data. The results revealed that majority of the heads of departments felt that flipped classroom promoted flexibility in managing study time (80%) and accessing course material (60%). Majority were also of the view that face - to - face learning promoted development of critical thinking (80%), understanding of course content (60%), collaboration and interaction with peers (60%), and engagement in class discussion (60%). Further, majority of the students reported that instructors in flipped classrooms ensured tasks were completed by discussing and assessing pre - class assignments. The study concluded that flipped learning was valued because it enhances access to course materials and study time flexibility whereas face - to - face learning was preferred as it promotes understanding of course content, collaboration and interaction with peers, engagement in classroom discussions and development of critical thinking. The study recommends that universities should adopt a blended learning model, which combines the strengths of the two approaches to optimize students’ academic performance.